The influence of learning motivation and learning activities on the Sociology learning outcomes of 11th-grade students at SMA Negeri 1 Mempawah Hulu - Yulius, Yulius; Bahari, Yohanes; Fatmawati, Fatmawati (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This research aims to clarify the influence of learning motivation and learning activities on the Sociology learning outcomes of 11th-grade students at SMA Negeri 1 Mempawah Hulu. The study will be conducted at SMA Negeri 1 in the Mempawah Hulu District. SMA Negeri 1 Mempawah Hulu is a high school located in the Mempawah Hulu District. The research adopts a quantitative approach with a survey method. Based on relevant research findings, it can be concluded that there is a significant relationship between motivation, learning activities, and learning outcomes. Instilling motivation and learning activities in students is crucial for them to develop their potential optimally. Student activity in the teaching and learning process is undoubtedly crucial to creating a lively classroom atmosphere and ensuring effective material absorption. To enhance student engagement and activity in the classroom, teachers need to plan appropriate teaching and learning activities to achieve learning objectives. One way to boost student learning motivation is by creating activity-based learning experiences.